Optimization of Public Health Centers Location in Bandar Lampung Using Integer Linear Programming - Rizka Efiyanti; Darsih Idayani (G-Tech: Jurnal Teknologi Terapan, 2025)
Public health centers are the primary healthcare services that play an essential role in public health services. Therefore, adequate facilities are needed to ensure that every individual receives proper healthcare services. Bandar Lampung City, the capital of Lampung Province, has a population of approximately 1,100,109 people. According to data from BPS (Statistics Indonesia), Bandar Lampung has a high life expectancy rate in Lampung, reaching 74.53%. To further improve this percentage, efforts are being made to ensure the equitable distribution of healthcare facilities across all regions of Bandar Lampung. This study aims to determine the optimal locations and number of public health centers in Bandar Lampung. Optimization is carried out using integer linear programming with the objective function of minimizing the number of public health centers while considering travel time and the maximum patient capacity each public health center can accommodate. The optimization model is formulated based on the set covering problem model and solved using the branch and bound method with LINGO software. The results indicate that the optimal number of public health centers needed to achieve an equitable distribution in Bandar Lampung is 43, covering 20 districts. This number is expected to fulfill the goal of ensuring equitable access to healthcare services through public health centers in Bandar Lampung.